Oxidative-Stress Resistance Mutants of Helicobacter pylori - Olczak, Adriana A. (American Society for Microbiology, 2002)
Within a large family of peroxidases, one member that catalyzes the reduction of organic peroxides to alcohols is known as alkyl hydroperoxide reductase, or AhpC. Gene disruption mutations in the gene encoding AhpC of Helicobacter pylori (ahpC) were generated by screening transformants under low-oxygen conditions. Two classes of mutants were obtained. Both types lack AhpC protein, but the major class (type I) isolated was found to synthesize increased levels (five times more than the wild type) of another proposed antioxidant protein, an iron-binding, neutrophil-activating protein (NapA). The other class of mutants, the minor class (type II), produced wild-type levels of NapA. The two types of AhpC mutants differed in their frequencies of spontaneous mutation to rifampin resistance and in their sensitivities to oxidative-stress chemicals, with the type I mutants exhibiting less sensitivity to organic hydroperoxides as well as having a lower mutation frequency. The napA promoter regions of the two types of AhpC mutants were identical, and primer extension analysis revealed their transcription start site to be the same as for the wild type. Gene disruption mutations were obtained in napA alone, and a double mutant strain (ahpC napA) was also created. All four of the oxidative-stress resistance mutants could be distinguished from the wild type in oxygen sensitivity or in some other oxidative-stress resistance phenotype (i.e., in sensitivity to stress-related chemicals and spontaneous mutation frequency). For example, growth of the NapA mutant was more sensitive to oxygen than that of the wild-type strain and both of the AhpC-type mutants were highly sensitive to paraquat and to cumene hydroperoxide. Of the four types of mutants, the double mutant was the most sensitive to growth inhibition by oxygen and by organic peroxides and it had the highest spontaneous mutation frequency. Notably, two-dimensional gel electrophoresis combined with protein sequence analysis identified another possible oxidative-stress resistance protein (HP0630) that was up-regulated in the double mutant. However, the transcription start site of the HP0630 gene was the same for the double mutant as for the wild type. It appears that H. pylori can readily modulate the expression of other resistance factors as a compensatory response to loss of a major oxidative-stress resistance component.